2020
DOI: 10.3389/fonc.2020.563938
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Target Peptide-Modified Erythrocyte Membrane-Enveloped PLGA Nanoparticles for the Treatment of Glioma

Abstract: Penetration of the blood-brain barrier (BBB) and the blood-brain tumor barrier (BBTB) remains a significant challenge for the delivery of drugs in the treatment of glioma. Therefore, the development of targeted preparations with the ability to penetrate the BBB and BBTB, and target gliomas, is an important approach if we are to improve the efficacy of glioma treatment. In the current study, an active targeting preparation based on PLGA nanoparticles coated with erythrocyte membranes (RBCNPs) and dual-modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…Euphorbia factor-L1 was used as model drug, and these NPs were taken up by the cells and showed the ability to cross both BBB and BBTB, thereby producing cytotoxic effects in vitro. Furthermore, in vivo studies supported these results and the prepared NPs could enter the brain, targeting tumor tissues and significantly extending the life span [ 82 ]. Subsequently, NERs of 5-FU for liver cancer treatment were prepared for improved pharmacokinetic and biodistribution of 5-FU.…”
Section: Applications Of Ners In Cancer Therapy and Diagnosismentioning
confidence: 93%
“…Euphorbia factor-L1 was used as model drug, and these NPs were taken up by the cells and showed the ability to cross both BBB and BBTB, thereby producing cytotoxic effects in vitro. Furthermore, in vivo studies supported these results and the prepared NPs could enter the brain, targeting tumor tissues and significantly extending the life span [ 82 ]. Subsequently, NERs of 5-FU for liver cancer treatment were prepared for improved pharmacokinetic and biodistribution of 5-FU.…”
Section: Applications Of Ners In Cancer Therapy and Diagnosismentioning
confidence: 93%
“…After the cells were injected, the needle was retained, for an extra 1 min, and then finally slowly pull out. After, the wound was sutured and the mice were fed normally [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peptides have attracted a significant amount of interest as ligands due to their small size, low toxicity, lack of immunogenicity, high selectivity, and wide inter/intracellular [ 165 ]. Peptide-modified PLGA-based NPs have recently been shown to successfully target various diseases, such as cancer [ 166 , 167 ] and atherosclerotic plaques [ 118 ].…”
Section: Surface Modification Strategiesmentioning
confidence: 99%
“…BBB-penetrating peptides, such as angiopep-2 peptide [ 174 ] and DWSW peptide [ 166 ], are exciting tools with which to target brain diseases. Preclinical studies of the systematic administration of these PLGA-based systems showed the ability of BBB-penetrating peptides to facilitate the entry of PLGA into the brain [ 166 ].…”
Section: Surface Modification Strategiesmentioning
confidence: 99%